Conductive polymer composition containing carbon nanotubes, and conductive polymer film

The conductive polymer composition, comprising polythiophene and carbon nanotubes, addresses the limitations of existing carbon nanotube dispersions by producing a conductive polymer film with superior electrical conductivity and stable dispersion.

JP2025069786APending Publication Date: 2025-05-01TOSOH CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023179728
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-18
Publication Date
2025-05-01

AI Technical Summary

Technical Problem

Existing carbon nanotube dispersions require high electrical conductivity but have room for improvement.

Method used

A conductive polymer composition containing 0.01 to 5% by mass of polythiophene with specific structural units and 0.016 to 0.5% by mass of carbon nanotubes, which is applied to a support and dried to produce a conductive polymer film with enhanced electrical conductivity.

Benefits of technology

The conductive polymer film achieves outstanding electrical conductivity and stable dispersion of carbon nanotubes, surpassing the performance of conventional carbon nanotube dispersions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025069786000001
    Figure 2025069786000001
  • Figure 2025069786000002
    Figure 2025069786000002
  • Figure 2025069786000003
    Figure 2025069786000003
Patent Text Reader

Abstract

To provide a conductive polymer film remarkably excellent in electrical conductivity and a conductive polymer composition for providing the conductive polymer film.SOLUTION: The conductive polymer composition is used which contains 0.01-5 mass% of a specific polythiophene (A) and 0.016-0.5 mass% of carbon nanotubes (B). The polythiophene (A) can be produced by polymerizing a thiophene monomer represented by the following general formula (3) in water or an alcohol solvent in the presence of an oxidizing agent, and subsequently performing acid treatment if necessary.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a conductive polymer composition containing carbon nanotubes, and a conductive polymer film. [Background technology]

[0002] Carbon nanotubes are tubes made of carbon atoms with a diameter of several nanometers and a length of several micrometers, and are characterized by excellent electrical conductivity, mechanical strength, and thermal conductivity, as well as a very small specific gravity. Due to these characteristics, the use of carbon nanotubes as inorganic fillers to improve the performance of composite materials has attracted attention.

[0003] To produce a carbon nanotube composite material, it is usually necessary to use a carbon nanotube dispersion in which carbon nanotubes are uniformly dispersed. However, carbon nanotubes have the property that they are difficult to disperse in water or organic solvents because they are in a bundled state due to strong interactions such as van der Waals forces in the solid state.

[0004] As a method for obtaining a carbon nanotube dispersion, a method in which polyisothianaphthenesulfonic acid is added to a mixture of carbon nanotubes and a solvent has been reported (for example, Patent Document 1). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2016-026983 A Summary of the Invention [Problem to be solved by the invention]

[0006] The carbon nanotube dispersion described in the background art has room for further improvement in that high electrical conductivity is required.

[0007] An object of one aspect of the present invention is to provide a conductive polymer film having remarkably excellent electrical conductivity and a conductive polymer composition for providing the conductive polymer film. [Means for solving the problem]

[0008] Means for Solving the Problems The present inventors conducted extensive research to solve the above problems, and as a result, found that the invention described below can solve the above problems, and completed the present invention.

[0009] An embodiment of the present invention includes the following [1] to

[10] .

[0010] [1] A conductive polymer composition comprising 0.01 to 5 mass % of polythiophene (A) containing at least two or more structural units selected from the group consisting of a structural unit represented by the following general formula (1) and a structural unit represented by the following general formula (2), and comprising 0.016 to 0.5 mass % of carbon nanotubes (B): [ka] [In the above general formulas (1) and (2), R 2 represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom, m represents an integer of 1 to 10, and n represents 0 or 1.

[0011] [2] The conductive polymer composition according to [1], wherein the carbon nanotubes (B) are at least one selected from the group consisting of single-walled carbon nanotubes, double-walled carbon nanotubes, and multi-walled carbon nanotubes.

[0012] [3] The conductive polymer composition according to [1], wherein the carbon nanotubes (B) are single-walled carbon nanotubes.

[0013] [4] The conductive polymer composition according to any one of [1] to [3], wherein the content of the polythiophene (A) is 0.05 to 0.8 mass %.

[0014] [5] The conductive polymer composition according to any one of [1] to [3], wherein the content of the carbon nanotubes (B) is 0.016 to 0.21 mass %.

[0015] [6] The conductive polymer composition according to any one of [1] to [5], wherein a compositional ratio of the polythiophene (A) to the carbon nanotubes (B) is 0.5 to 3 parts by mass of the carbon nanotubes (B) per 1 part by mass of the polythiophene (A).

[0016] [7] The conductive polymer composition according to any one of [1] to [5], wherein a compositional ratio of the polythiophene (A) to the carbon nanotubes (B) is 1 to 2.5 parts by mass of the carbon nanotubes (B) per 1 part by mass of the polythiophene (A).

[0017] [8] A method for producing a conductive polymer film, comprising applying the conductive polymer composition according to any one of [1] to [7] onto a support and then drying the applied conductive polymer composition.

[0018] [9] A conductive polymer film comprising: a polythiophene (A) containing at least one structural unit selected from the group consisting of a structural unit represented by the following general formula (1) and a structural unit represented by the following general formula (2); and a carbon nanotube (B), wherein the compositional ratio of the polythiophene (A) to the carbon nanotube (B) is 0.5 to 3 parts by mass of the carbon nanotube (B) per part by mass of the polythiophene (A). [ka] [In the above general formulas (1) and (2), R2 represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom, m represents an integer of 1 to 10, and n represents 0 or 1.

[0019]

[10] The conductive polymer film according to [9], wherein a composition ratio of the polythiophene (A) to the carbon nanotubes (B) is 1 to 2.5 parts by mass of the carbon nanotubes (B) per 1 part by mass of the polythiophene (A). Effect of the Invention

[0020] The conductive polymer composition according to one embodiment of the present invention can provide a conductive polymer film having remarkably excellent electrical conductivity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The present invention will be described in detail below. In this specification, the term "A to B" indicating a range of numerical values ​​means "A or more and B or less".

[0022] Various carbon nanotube dispersions have been developed for composite material applications, but the dispersants used in these dispersions can sometimes reduce the excellent electrical conductivity of the carbon nanotubes themselves.

[0023] Details will be described later using specific examples, but the conductive polymer composition according to one embodiment of the present invention contains carbon nanotubes and has the remarkable effect of achieving both carbon nanotube dispersion stability and excellent electrical conductivity.

[0024] The conductive polymer composition according to one embodiment of the present invention is characterized by containing 0.01 to 5 mass % of polythiophene (A) including at least two or more structural units selected from the group consisting of a structural unit represented by the following general formula (1) and a structural unit represented by the following general formula (2), and containing 0.016 to 0.5 mass % of carbon nanotubes (B):

[0025] [ka]

[0026] [In the above general formulas (1) and (2), R 2 represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom, m represents an integer of 1 to 10, and n represents 0 or 1.

[0027] In the above general formulas (1) and (2), R 2 represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom.

[0028] The linear or branched alkyl group having 3 to 6 carbon atoms is not particularly limited, but examples thereof include an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an isopentyl group, a neopentyl group, a tert-pentyl group, a cyclopentyl group, an n-hexyl group, a 2-ethylbutyl group, and a cyclohexyl group.

[0029] The above R 2 With regard to , in terms of obtaining a conductive polymer film exhibiting high conductivity, a hydrogen atom, a methyl group, an ethyl group, or a fluorine atom is preferable, and a hydrogen atom or a methyl group is more preferable.

[0030] In the above general formulas (1) and (2), m represents an integer of 1 to 10, and is preferably an integer of 1 to 6, more preferably an integer of 1 to 4, and even more preferably 2 or 3, in that a conductive polymer film exhibiting high conductivity can be obtained.

[0031] In the above general formulas (1) and (2), n represents 0 or 1, and is preferably 1 in that a conductive polymer film exhibiting high conductivity can be obtained.

[0032] The structural unit represented by the above general formula (2) represents the doped state of the structural unit represented by the above general formula (1).

[0033] Dopants that cause an insulator-metal transition by doping can be divided into acceptors and donors. The former enters the vicinity of the polymer chain of a conductive polymer by doping and takes away π electrons from the conjugated system of the main chain. As a result, a positive charge (hole) is injected into the main chain, so it is also called a p-type dopant. Conversely, the latter donates electrons to the conjugated system of the main chain, and these electrons move through the conjugated system of the main chain, so it is also called an n-type dopant.

[0034] In one embodiment of the present invention, the dopant is a sulfo or sulfonate group covalently bonded within the polymer molecule, and is a p-type dopant. Polymers that exhibit conductivity without the addition of an external dopant are called self-doped polymers.

[0035] The polythiophene (A) according to one embodiment of the present invention can be produced by polymerizing a thiophene monomer represented by the following general formula (3) in water or an alcohol solvent in the presence of an oxidizing agent, and then optionally treating with an acid.

[0036] [ka]

[0037] [In the above general formula (3), M represents a hydrogen ion, an ammonium ion, an organic ammonium ion, or a metal ion. 2 represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom, m represents an integer of 1 to 10, and n represents 0 or 1.

[0038] The metal ion represented by M in general formula (3) is not particularly limited, but examples thereof include transition metal ions, precious metal ions, non-ferrous metal ions, alkali metal ions (e.g., Li ions, Na ions, and K ions), and alkaline earth metal ions.

[0039] The organic ammonium ion represented by M in the general formula (3) is not particularly limited, but examples thereof include a methylammonium ion, a dimethylammonium ion, a trimethylammonium ion, an ethylammonium ion, a diethylammonium ion, a triethylammonium ion, a hydroxyethylammonium ion, an N,N-bishydroxyethylammonium ion, and an N,N,N-trishydroxyethylammonium ion.

[0040] From the viewpoint of ease of production of the polythiophene (A), M is preferably a hydrogen atom or an alkali metal ion, and more preferably a Na ion or a K ion.

[0041] R in general formula (3) 2 The definitions and preferred ranges of m and n are as follows: 2 The definitions and preferred ranges of , m, and n are the same as those of .

[0042] The thiophene monomer represented by the above general formula (3) is not particularly limited, but specifically includes 6-(2,3-dihydro-thieno[3,4-b][1,4]dioxin-2-yl)hexane-1-sulfonic acid, sodium 6-(2,3-dihydro-thieno[3,4-b][1,4]dioxin-2-yl)hexane-1-sulfonate, lithium 6-(2,3-dihydro-thieno[3,4-b][1,4]dioxin-2-yl)hexane-1-sulfonate, 6-(2,3-dihydro-thieno[3,4-b][1,4]dioxin-2-yl)hexane-1-sulfonate, ) hexane-1-sulfonic acid potassium, 8-(2,3-dihydro-thieno[3,4-b][1,4]dioxin-2-yl)octane-1-sulfonic acid, 8-(2,3-dihydro-thieno[3,4-b][1,4]dioxin-2-yl)octane-1-sulfonic acid sodium, 8-(2,3-dihydro-thieno[3,4-b][1,4]dioxin-2-yl)octane-1-sulfonic acid potassium, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-propanesulfonic acid sodium, 3-[(2 ,3-Dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-propanesulfonic acid potassium salt, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonic acid sodium salt, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-ethyl-1-propanesulfonic acid sodium salt, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-propyl-1- Sodium propanesulfonate, sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-butyl-1-propanesulfonate, sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-pentyl-1-propanesulfonate, sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-hexyl-1-propanesulfonate, sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-isopropyl-1-propanesulfonic acid sodium salt, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-isobutyl-1-propanesulfonic acid sodium salt, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-isopentyl-1-propanesulfonic acid sodium salt, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]- Sodium 1-fluoro-1-propanesulfonate, potassium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonic acid, ammonium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate, Hydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate triethylammonium, 4-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-butanesulfonate sodium, 4-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-butanesulfonate potassium, 4-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-butanesulfonate Examples include sodium 1-methyl-1-butanesulfonate, potassium 4-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-butanesulfonate, sodium 4-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-fluoro-1-butanesulfonate, and potassium 4-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-fluoro-1-butanesulfonate.

[0043] When the polymer obtained by polymerization of the thiophene monomer represented by the general formula (3) is a salt of a metal ion (when M is a metal ion), M can be converted to a hydrogen ion by treating the obtained polymer with an acid (for example, by ion exchange with a cation exchange resin). That is, even when M in the general formula (3) is a metal ion, it is possible to produce a polythiophene (A) containing at least one structural unit selected from the group consisting of the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2).

[0044] In the conductive polymer composition according to one embodiment of the present invention, the content (concentration) of the polythiophene (A) containing at least one structural unit selected from the group consisting of the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2) is in the range of 0.01 to 5 mass %. In order to obtain a conductive polymer film exhibiting high conductivity, the content (concentration) of the polythiophene (A) in the conductive polymer composition according to one embodiment of the present invention is preferably in the range of 0.03 to 2 mass %, more preferably in the range of 0.05 to 0.8 mass %, and even more preferably in the range of 0.05 to 0.5 mass %.

[0045] The conductive polymer composition according to one embodiment of the present invention is characterized in that it contains carbon nanotubes (B) and has a content (concentration) of 0.016 to 0.5 mass %. The content (concentration) of the carbon nanotubes (B) is preferably 0.016 to 0.21 mass %. This characteristic allows a conductive polymer film with high conductivity to be obtained.

[0046] The carbon nanotube (B) refers to a substance in which a six-membered ring network made of carbon is in the form of a single-layer or multi-layer coaxial ring. Although not particularly limited, specifically, at least one selected from the group consisting of single-walled carbon nanotubes, double-walled carbon nanotubes, and multi-walled carbon nanotubes is preferred. Single-walled carbon nanotubes are more preferred in that they can provide a conductive polymer film exhibiting high conductivity.

[0047] The diameter of the single-walled carbon nanotube (meaning the "average diameter") is not particularly limited, but may be, for example, 20 nm or less, preferably 10 nm or less, and more preferably 5 nm or less. The lower limit of the diameter of the single-walled carbon nanotube is not particularly limited, but may be, for example, 0.4 nm or more, or 0.5 nm or more. The diameter of the single-walled carbon nanotube is preferably in the range of 0.4 to 20 nm, more preferably in the range of 0.4 to 10 nm, more preferably in the range of 0.5 to 5 nm, and more preferably in the range of 0.8 to 3 nm.

[0048] Regarding such carbon nanotubes (B), commercially available products can be used as they are, or those prepared by a known method can be used. Note that, although carbon nanotubes (B) are provided as a powder solid, a water dispersion, an organic solvent dispersion, or the like, in the conductive polymer composition according to one embodiment of the present invention, the powder solid is preferred.

[0049] In the conductive polymer composition according to one embodiment of the present invention, from the viewpoint of the conductivity of the resulting conductive polymer film, the composition ratio of polythiophene (A) to carbon nanotubes (B) is preferably 0.2 to 4 parts by mass of carbon nanotubes (B) per part by mass of polythiophene (A), more preferably 0.3 to 3 parts by mass of carbon nanotubes (B), more preferably 0.5 to 3 parts by mass of carbon nanotubes (B), more preferably 1 to 3 parts by mass of carbon nanotubes (B), and even more preferably 1 to 2.5 parts by mass of carbon nanotubes (B).

[0050] The conductive polymer composition according to one embodiment of the present invention may further contain a compound (C) capable of forming an ion pair with the sulfonic acid group of the polythiophene (A) containing at least two or more structural units selected from the group consisting of the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2), in order to have excellent conductivity and coatability. The compound (C) capable of forming an ion pair with the sulfonic acid group is not particularly limited, and examples thereof include an alkali metal compound, ammonia, an organic amine compound, and a quaternary ammonium salt. These compounds (C) react with the sulfonic acid group of the polythiophene (A) to form an alkali metal ion salt, an ammonium ion salt, an organic ammonium ion salt, or a quaternary ammonium ion salt of the polythiophene (A), respectively.

[0051] The above-mentioned alkali metal compound is not particularly limited, but examples thereof include alkali metal hydroxides (such as lithium hydroxide, potassium hydroxide, sodium hydroxide, rubidium hydroxide, and cesium hydroxide).

[0052] The alkali metal ion salt of polythiophene (A) can be prepared by incorporating the alkali metal compound into the conductive polymer composition according to one embodiment of the present invention. In this case, the polythiophene (A) is a polythiophene containing at least one structural unit selected from the group consisting of structural units represented by general formula (1') and structural units represented by general formula (2') described below, and M is an alkali metal ion. The alkali metal ion is not particularly limited, but examples thereof include lithium ion, potassium ion, sodium ion, rubidium ion, and cesium ion.

[0053] The organic amine compound is not particularly limited, but examples thereof include primary, secondary, or tertiary amine compounds having a total carbon number of 1 to 30. More specifically, for example, methylamine, dimethylamine, trimethylamine, ethylamine, triethylamine, n-propylamine, isopropylamine, n-butylamine, isobutylamine, diisobutylamine, triisobutylamine, hexylamine, dihexylamine, trihexylamine, octylamine, dioctylamine, trioctylamine, decylamine, didecylamine, tridecylamine, (2-ethylhexyl)amine, Examples of the amine include amine, bis(2-ethylhexyl)amine, tris(2-ethylhexyl)amine, aminoethanol, dimethylaminoethanol, methylaminoethanol, diethanolamine, N-methyldiethanolamine, triethanolamine, 3-amino-1,2-propanediol, 3-methylamino-1,2-propanediol, 3-dimethylamino-1,2-propanediol, 1,4-butanediamine, triisobutylamine, triisopentylamine, triisooctylamine, imidazole, N-methylimidazole, 1,2-dimethylimidazole, pyridine, picoline, and lutidine.

[0054] By incorporating the organic amine compound into the conductive polymer composition according to one embodiment of the present invention, the organic amine compound reacts with the polythiophene (A) to form an organic ammonium ion, and an organic ammonium ion salt of the polythiophene (A) is prepared. At this time, the polythiophene (A) is a polythiophene containing at least one structural unit selected from the group consisting of a structural unit represented by general formula (1') and a structural unit represented by general formula (2') described below, and M is an organic ammonium ion.

[0055] The organic ammonium ion is not particularly limited, and examples thereof include primary, secondary, and tertiary ammonium ions having a total carbon number of 1 to 30. More specifically, examples thereof include methylammonium, dimethylammonium, trimethylammonium, ethylammonium, triethylammonium, normal-propylammonium, isopropylammonium, normal-butylammonium, isobutylammonium, diisobutylammonium, triisobutylammonium, hexylammonium, dihexylammonium, trihexylammonium, octylammonium, dioctylammonium, trioctylammonium, decylammonium, didecylammonium, tridecylammonium, (2-ethylhexyl)ammonium, bis(2-ethylhexyl)ammonium, and tris(2-ethylhexyl)ammonium. ammonium, 2-hydroxyethylammonium, N,N-dimethyl-N-(2-hydroxyethyl)ammonium, N-methyl-N-(2-hydroxyethyl)ammonium, di(2-hydroxyethyl)ammonium, N-methyl-N,N-di(2-hydroxyethyl)ammonium, N,N,N-tri(2-hydroxyethyl)ammonium, 2,3-dihydroxypropylammonium, N-methyl-N-(2,3-dihydroxypropyl)ammonium, N,N-dimethyl-N-(2,3-dihydroxypropyl)ammonium, 1,4-butanediammonium, triisobutylammonium, triisopentylammonium, triisooctylammonium, imidazole cation, N-methylimidazole cation, 1,2-dimethylimidazole cation, pyridinium ion, picolinium ion, or lutidinium ion.

[0056] The above-mentioned quaternary ammonium compound is not particularly limited, but examples thereof include tetramethylammonium chloride, tetraethylammonium chloride, tetra-n-propylammonium chloride, tetra-n-butylammonium chloride, and tetra-n-hexylammonium chloride.

[0057] By incorporating the quaternary ammonium compound into the conductive polymer composition of the present invention, the quaternary ammonium compound reacts with the polythiophene (A) to form a quaternary ammonium ion, and a quaternary ammonium ion salt of the polythiophene (A) is prepared. At this time, the polythiophene (A) is a polythiophene containing at least one structural unit selected from the group consisting of a structural unit represented by general formula (1') and a structural unit represented by general formula (2') described below, and M is a quaternary ammonium ion. The quaternary ammonium ion is not particularly limited, and examples thereof include tetramethylammonium ion, tetraethylammonium ion, tetra-n-propylammonium ion, tetra-n-butylammonium ion, and tetra-n-hexylammonium ion.

[0058] In the conductive polymer composition according to one embodiment of the present invention, the content of the compound (C) is preferably 0.001 to 20 mass %, and in terms of excellent surface resistivity (low resistance), the content is more preferably 0.001 to 15 mass %, and even more preferably 0.003 to 10 mass %.

[0059] When the conductive polymer composition according to one embodiment of the present invention contains the above compound (C), the polythiophene (A) containing at least one structural unit selected from the group consisting of structural units represented by the above general formula (1) and structural units represented by the general formula (2) can be described as a polythiophene (A) containing at least one structural unit selected from the group consisting of structural units represented by the following general formula (1') and structural units represented by the general formula (2').

[0060] [ka]

[0061] [In the above general formula (1') and general formula (2'), R 2represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom, m represents an integer of 1 to 10, and n represents 0 or 1. M represents a hydrogen ion, an alkali metal ion, an ammonium ion, an organic ammonium ion, or a quaternary ammonium ion.]

[0062] In the above general formula (1') and general formula (2'), R 2 The definitions and preferred ranges of m and n are as shown in the above general formula (1) and general formula (2) R 2 , m, and n have the same definitions and preferred ranges.

[0063] The alkali metal ion, ammonium ion, organic ammonium ion, and quaternary ammonium ion in the above M are as described above. In addition, in the polythiophene (A) containing at least one structural unit selected from the group consisting of the structural unit represented by the above general formula (1') and the structural unit represented by the general formula (2'), M does not need to be a single unit, and multiple types of M can coexist.

[0064] In terms of excellent surface resistance (low resistance), the conductive polymer composition according to one embodiment of the present invention has a pH in the range of preferably 1.0 to 10.0, more preferably 1.5 to 8.0, and even more preferably 1.5 to 7.5. The pH can be controlled by the type and content of the compound (C) described above.

[0065] A polythiophene containing at least one structural unit selected from the group consisting of structural units represented by general formula (1') and structural units represented by general formula (2') can be produced by mixing polythiophene (A) containing at least one structural unit selected from the group consisting of structural units represented by general formula (1) and structural units represented by general formula (2) above with a compound (C) capable of forming an ion pair with the sulfonic acid group of polythiophene (A) (e.g., the above-mentioned alkali metal compound, ammonia, amine compound, or quaternary ammonium compound).

[0066] In one embodiment of the present invention, the conductivity of the polythiophene (A) is not particularly limited, but the conductivity (electrical conductivity) in a film state is preferably 10 S / cm or more, more preferably 50 S / cm or more, and even more preferably 100 S / cm or more.

[0067] Note that the polythiophene (A) according to one embodiment of the present invention may be one synthesized based on publicly known information.

[0068] The conductive polymer composition according to one embodiment of the present invention is not particularly limited, but may contain one or more solvents (D) selected from the group consisting of organic solvents and water, and preferably contains one or more solvents (D) selected from the group consisting of organic solvents and water in terms of excellent operability.

[0069] The above-mentioned solvent (D) may be constituted by a solvent for the polythiophene (A) containing at least one structural unit selected from the group consisting of the structural unit represented by the above-mentioned general formula (1) and the structural unit represented by the general formula (2), or a solvent accompanying the carbon nanotubes (B), or a separate solvent (D) may be added and contained in the conductive polymer composition according to one aspect of the present invention.

[0070] The water is not particularly limited, but examples thereof include purified water, distilled water, ion-exchanged water, pure water, etc. It is preferable to use water of as high purity as possible as the added solvent (D).

[0071] The organic solvent is not particularly limited, but examples thereof include alcohols, ketones, ethers, aromatic compounds, and more specific examples thereof include methanol, ethanol, propanol, butanol, methoxyethanol, ethoxyethanol, butoxyethanol, ethylene glycol, propylene glycol monomethyl ether, propylene glycol monoethyl ether, methyl ethyl ketone, methyl isobutyl ketone, 2-pyrrolidone, N-methylpyrrolidone, dioxane, toluene, xylene, and chlorobenzene.

[0072] The content (concentration) of the solvent (D) in the conductive polymer composition according to one embodiment of the present invention is not particularly limited, but from the viewpoint of excellent workability, it is preferably in the range of 85 to 99.9 mass %, more preferably 90 to 99.9 mass %, and still more preferably 95 to 99.8 mass %.

[0073] The conductive polymer composition according to one embodiment of the present invention may contain additives (E) other than those described above.

[0074] The additive (E) is not particularly limited, but may be, for example, a binder, a surfactant, etc. The additive (E) may be used alone or in combination of two or more.

[0075] The binder is not particularly limited, but is preferably, for example, a water-soluble resin, and more specific examples include polyvinyl alcohol, polyvinylpyrrolidone, cellulose, a water-soluble polyester resin compound, a water-soluble polyurethane resin compound, or a mixture of a polyhydric alcohol and an organic acid having two or more carboxyl groups.

[0076] Examples of the water-soluble polyester resin compound include polyethylene terephthalate, polytrimethylene terephthalate, etc. The water-soluble polyester resin compound may be a self-emulsifying type or a reinforced emulsifying type, but is preferably a self-emulsifying type water-soluble polyester resin compound from the viewpoint of water resistance and solvent resistance.

[0077] Examples of the water-soluble polyester resin compound include Vylonal (registered trademark, manufactured by Toyobo Co., Ltd.), PESRESIN S (manufactured by Takamatsu Oil Co., Ltd.), PESRESIN A (manufactured by Takamatsu Oil Co., Ltd.), Pluscoat (registered trademark, manufactured by GOO Chemical Co., Ltd.), Aronmelt (registered trademark, manufactured by Toagosei Co., Ltd.), and Watersol (registered trademark, manufactured by DIC Corporation), which are commercially available and easily available.

[0078] The above water-soluble polyester resin compounds may be used alone or in combination of two or more.

[0079] The above-mentioned water-soluble polyurethane resin compound is mainly used in industrial applications as a urethane resin emulsion, and may be a self-emulsifying type or a reinforced emulsion type, but is preferably a self-emulsifying water-soluble polyurethane resin compound from the viewpoint of water resistance and solvent resistance. The self-emulsifying type may be an anionic type, a cationic type, or a nonionic type, but any of them may be used. In addition, the water-soluble polyurethane resin compound is not particularly limited, but may be a polyether type, a polyester type, or a polycarbonate type.

[0080] Examples of water-soluble polyurethane resin compounds that can be easily obtained commercially include U-coat (registered trademark, manufactured by Sanyo Chemical Industries, Ltd.), Permarin (registered trademark, manufactured by Sanyo Chemical Industries, Ltd.), Euprene (registered trademark, manufactured by Sanyo Chemical Industries, Ltd.), NeoRez (registered trademark, manufactured by Covestro Coating Resins), Adeka Bonditer (registered trademark, manufactured by ADEKA Corporation), Pascol (registered trademark, manufactured by Meisei Chemical Industry Co., Ltd.), and Hydran (registered trademark, manufactured by DIC Corporation).

[0081] The above water-soluble polyurethane resin compounds can be used alone or in combination of two or more.

[0082] The polyhydric alcohol is not particularly limited, but examples thereof include erythritol and pentaerythritol.

[0083] The organic acid having two or more carboxyl groups is not particularly limited, but examples thereof include adipic acid and phthalic acid.

[0084] The surfactant is not particularly limited, but examples of the surfactant that can be used include anionic surfactants, cationic surfactants, nonionic surfactants, amphoteric surfactants, fluorine-based surfactants, and silicone-based surfactants, and more preferably at least one selected from the group consisting of nonionic surfactants and amphoteric surfactants.

[0085] The anionic surfactant is not particularly limited, but examples thereof include sodium lauryl alcohol sulfate, sodium dodecylbenzenesulfonate, and the like.

[0086] The cationic surfactant is not particularly limited, but a commercially available product can be used, or a generally known product can be separately produced and used.

[0087] The nonionic surfactant is not particularly limited, but examples thereof include polyethylene glycol type surfactants, acetylene glycol type surfactants, polyhydric alcohol type surfactants, and polymer type nonionic surfactants.

[0088] The polyethylene glycol surfactant is not particularly limited, but examples thereof include ethylene oxide adducts of higher alcohols, ethylene oxide adducts of alkylphenols, ethylene oxide adducts of fatty acids, ethylene oxide adducts of polyhydric alcohol fatty acid esters, ethylene oxide adducts of higher alkylamines, ethylene oxide adducts of fats and oils, and ethylene oxide adducts of polypropylene glycols.

[0089] The acetylene glycol surfactant is not particularly limited, but examples thereof include 2,4,7,9-tetramethyl-5-decyne-4,7-diol, Surfynol (registered trademark, manufactured by Air Products Co., Ltd.), and Olfine (registered trademark, manufactured by Nissin Chemical Industry Co., Ltd.).

[0090] The polyhydric alcohol surfactant is not particularly limited, but examples thereof include fatty acid esters of glycerol, fatty acid esters of pentaerythritol, fatty acid esters of sorbitol and sorbitan, fatty acid esters of sucrose, alkyl ethers of higher alcohols, and fatty acid amides of alkanolamines.

[0091] The amphoteric surfactant is not particularly limited, but may be, for example, a betaine-type amphoteric surfactant, such as, for example, alkyl dimethyl betaine, lauryl dimethyl betaine, stearyl dimethyl betaine, or lauryl dihydroxyethyl betaine.

[0092] The above-mentioned fluorosurfactant is not particularly limited as long as it has a perfluoroalkyl group, but examples thereof include Pluscoat (registered trademark) RY-2, perfluoroalkanes, perfluoroalkyl carboxylic acids, perfluoroalkyl sulfonic acids, and perfluoroalkyl ethylene oxide adducts.

[0093] The silicone surfactant is not particularly limited, but examples thereof include polyether-modified polydimethylsiloxane, polyetherester-modified polydimethylsiloxane, hydroxyl group-containing polyether-modified polydimethylsiloxane, acrylic group-containing polyether-modified polydimethylsiloxane, acrylic group-containing polyester-modified polydimethylsiloxane, perfluoropolyether-modified polydimethylsiloxane, perfluoropolyester-modified polydimethylsiloxane, and silicone-modified acrylic compounds.

[0094] The fluorine-based surfactant or silicone-based surfactant is effective as a leveling agent to improve the flatness of the coating film.

[0095] In the conductive polymer composition according to one embodiment of the present invention, the content of the additive (E) is preferably 0 (zero) mass% in order to obtain a conductive polymer film exhibiting high conductivity. On the other hand, when excellent operability is required, the content is preferably 0.001 to 20 mass%, more preferably 0.01 to 15 mass%, and even more preferably 0.1 to 10 mass%.

[0096] The method for preparing the conductive polymer composition according to one embodiment of the present invention is not particularly limited, but may be, for example, a method of mixing the solution or solid of the polythiophene (A) with the solid or solvent dispersion of the carbon nanotubes (B). At this time, the compound (C), the solvent (D), and / or the additive (E) may be added and mixed as necessary. It is preferable to mix each material after adding and dissolving it in the solvent (D), but there is no particular limit to the order in which the materials are added and mixed. By mixing these materials in any order, the conductive polymer composition according to one embodiment of the present invention can be prepared.

[0097] Here, the temperature during mixing is not particularly limited, but may be, for example, room temperature to heated. The temperature is preferably 0° C. or higher and 100° C. or lower. In this specification, room temperature refers to a temperature of 15 to 25° C.

[0098] The atmosphere in which the mixture is mixed is not particularly limited, and may be air or an inert gas atmosphere.

[0099] In addition, when mixing, ultrasonic irradiation or homogenization (for example, using a mechanical homogenizer, ultrasonic homogenizer, high-pressure homogenizer, etc.) may be performed in addition to a general mixing and dissolving operation using a stirrer tip or stirring blade. When homogenization is performed, it is preferable to perform it while cooling or heating in order to prevent thermal deterioration of the polymer. The above mixing can be performed by a single operation or device, or can be performed using multiple operations or devices. Examples of the method of mixing using multiple operations or devices include a method of simultaneously performing a mixing operation using a stirring blade and a mixing operation using an ultrasonic homogenizer.

[0100] The viscosity (20° C.) of the conductive polymer composition according to one embodiment of the present invention is preferably 200 mPa·s or less, more preferably 100 mPa·s or less, and further preferably 50 mPa·s or less.

[0101] The concentration of each component in the conductive polymer composition according to one embodiment of the present invention may be adjusted by the blending ratio, or may be adjusted by concentrating or diluting after blending. The concentrating method may be a method of distilling off the solvent under reduced pressure, or a method of using an ultrafiltration membrane.

[0102] In the conductive polymer composition according to one embodiment of the present invention, the concentration of all components excluding the solvent (D) is preferably in the range of 0.1 to 20 mass%, more preferably in the range of 0.3 to 15 mass%, and still more preferably in the range of 0.5 to 10 mass%.

[0103] By using the conductive polymer composition according to one embodiment of the present invention, a conductive polymer film having high electrical conductivity and / or electromagnetic wave shielding effect can be produced.

[0104] The method for forming a conductive polymer film from the conductive polymer composition according to an embodiment of the present invention is not particularly limited, but may be, for example, a method in which the conductive polymer composition according to an embodiment of the present invention is applied to a support and then dried.

[0105] The support is not particularly limited as long as it is capable of applying the conductive polymer composition according to an embodiment of the present invention, and examples thereof include polymer substrates and inorganic substrates. Examples of polymer substrates include thermoplastic resins, nonwoven fabrics, paper, and resist film substrates. Examples of thermoplastic resins include polyethylene, polypropylene, polyethylene terephthalate, polyacrylate, and polycarbonate. Examples of nonwoven fabrics include natural fibers and synthetic fibers. Examples of paper include those mainly composed of general cellulose. Examples of inorganic substrates include glass, glass fibers, ceramics, aluminum oxide, and tantalum oxide.

[0106] Examples of the method for applying the conductive polymer composition include casting, dipping, bar coating, dispenser, roll coating, gravure coating, flexographic printing, screen printing, and offset printing.

[0107] The drying temperature for the coating film is not particularly limited as long as it is a temperature at which a uniform conductive polymer film is obtained and is equal to or lower than the heat resistance temperature of the substrate, but is preferably in the range of room temperature to 300°C, more preferably in the range of room temperature to 250°C, and even more preferably in the range of room temperature to 200°C.

[0108] The drying atmosphere may be any of air, inert gas, vacuum, and reduced pressure, but from the viewpoint of preventing deterioration of the conductive polymer film, an inert gas atmosphere such as nitrogen or argon is preferred.

[0109] The thickness of the resulting conductive polymer film is not particularly limited, but is preferably 10 -3 ~10 3 The range of 10 μm is preferable. -3 ~10 2 μm.

[0110] A conductive polymer film obtained from the conductive polymer composition according to one aspect of the present invention has excellent conductivity. The conductive polymer film is used, for example, as a solid electrolyte or a transparent electrode of a capacitor.

[0111] That is, the conductive polymer film is characterized by containing polythiophene (A) containing at least one structural unit selected from the group consisting of structural units represented by the general formula (1) above and structural units represented by the general formula (2) above, and carbon nanotubes (B), and may contain components that the conductive polymer composition described above may contain.

[0112] In the above-mentioned conductive polymer film, the composition ratio of polythiophene (A) to carbon nanotubes (B) is preferably 0.2 to 4 parts by mass of carbon nanotubes (B) per 1 part by mass of polythiophene (A), more preferably 0.3 to 3 parts by mass of carbon nanotubes (B), even more preferably 0.5 to 3 parts by mass of carbon nanotubes (B), still more preferably 1 to 3 parts by mass of carbon nanotubes (B), and even more preferably 1 to 2.5 parts by mass of carbon nanotubes (B).

[0113] The present invention is not limited to the above-described embodiments, and various modifications are possible within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention. EXAMPLES

[0114] Examples of the present invention will be described below. The analytical instruments and measurement methods used in the examples are listed below.

[0115] [GC measurement] Equipment: Shimadzu, GC-2014 [NMR measurement] Equipment: VARIAN, Gemini-200 [Surface resistance measurement] Apparatus: Mitsubishi Chemical Corporation Loresta (registered trademark) GP MCP-T600 or Mitsubishi Chemical Corporation Hiresta (registered trademark) UX MCP-HT8000 [Film thickness measurement] Device: DEKTAK (registered trademark) XT manufactured by BRUKER [Viscosity measurement] Complete Viscometer / BROOKFIELD(registered trademark) VISCOMETER DV-1 Prime [Particle size measurement] Equipment: Nikkiso Microtrac (registered trademark) Nanotrac (registered trademark) UPA-UT151

[0116] [Conductivity measurement of self-doped conductive polymer] 0.5 ml of the solution containing the self-doped conductive polymer was cast onto a 25 mm square alkali-free glass plate that had been UV-ozone-treated, dried on a hot plate at 60°C for 30 minutes, and then heated at 200°C for 30 minutes to obtain a conductive polymer film. The surface resistance and film thickness of the obtained conductive polymer film were measured as described above. The conductivity was calculated from the surface resistance and film thickness according to the following formula.

[0117] [conductivity] Conductivity [S / cm]=10 4 / (surface resistance value [Ω / □] × film thickness [μm])

[0118] [Method of evaluating dispersion state] The dispersion state was evaluated as good when no aggregates were visually observed in the solution of the conductive polymer composition containing the synthesized carbon nanotubes.

[0119] Synthesis example 1. Synthesis of sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate [compound represented by formula (6) below]. In a nitrogen atmosphere, 0.437g (10.9mmol) of 60% sodium hydride and 37ml of toluene were charged into a 100ml eggplant flask, and then 1.52g (8.84ml) of (2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methanol was added to obtain a reaction solution. The reaction solution was then heated to reflux temperature and stirred at the same temperature for 1 hour. A mixture of 1.21g (8.89mmol) of 2,4-butanesultone and 10ml of toluene was then added dropwise and stirred at the same temperature for 2 hours. After cooling, the reaction solution was added dropwise to 160ml of acetone to perform reprecipitation. The resulting powder was filtered and vacuum dried to obtain 1.82g of pale yellow powder in a yield of 62%. NMR measurement confirmed that this was sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate represented by the following formula (6).

[0120] [ka]

[0121] 1 H-NMR(D2O)δ(ppm);6.67(s,2H),4.54-4.60(m,1H),4.45(dd,1H,J=12.0,2.2Hz),4.26(dd,1H,J=12 .0,6.8Hz),3.90-3.81(m,4H),3.10-3.18(m,1H),2.30-2.47(m,1H),1.77-1.92(m,1H),1.45(d,3H) 13 C-NMR(D2O)δ(ppm);14.91,31.22,53.13,66.18,69.18,73.29,73.36,100.81,100.94,140.88,141.06

[0122] Synthesis example 2. Synthesis of polythiophene (A) [polymer containing a structural unit represented by the following formula (7) or (8)]. In a 500 ml separable flask, 10 g (30 mmol) of 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonic acid sodium salt (hereinafter referred to as "monomer a") synthesized according to Synthesis Example 1 and 150 g of water were charged. After dissolution, 2.94 g (18.1 mmol) of anhydrous iron(III) chloride was added at room temperature to prepare a reaction liquid, which was then stirred for 20 minutes. Then, a mixed solution consisting of 14.5 g (60.4 mmol) of sodium persulfate and 100 g of water was added dropwise to the reaction liquid while controlling the liquid temperature of the reaction liquid to be 30° C. or less. After completion of the addition, the mixture was stirred at room temperature for 3 hours, and then the reaction liquid was added dropwise to 800 g of acetone to precipitate a black Na-type polymer. The polymer was filtered and dried under vacuum to obtain 18.0 g of a crude polymer of sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate (Na-type polythiophene (A)).

[0123] Next, 700 g of an aqueous solution prepared by adding water to 14.5 g of the above Na-type polythiophene (A) to prepare a 2% by mass solution was passed through a column packed with 200 ml of cation exchange resin Lewatit (registered trademark) MonoPlus S100 (H-type) (spatial velocity = 1.1) to obtain 738 g of an aqueous solution of H-type polymer (H-type polythiophene (A)).

[0124] Furthermore, the aqueous solution was purified by cross-flow ultrafiltration (filter = Vivaflow 200, molecular weight cutoff = 5,000, permeability = 5) to obtain 698 g of a deep ultramarine solution of a polymer (H-type polythiophene (A1)) consisting of a structural unit represented by the following formula (7) or formula (8). The concentration of H-type polythiophene (A1) contained in the polymer solution was 0.74 mass%. The H-type polythiophene (A1) contained 44 ppm and 12 ppm of iron ions and sodium ions, respectively, based on the mass of H-type polythiophene (A1).

[0125] [ka]

[0126] [ka]

[0127] Synthesis Example 3 The same operation as in Synthesis Example 2 was carried out except that the amount of monomer a used was changed from 10 g to 10.5 g, and the amounts of anhydrous iron (III) chloride and sodium persulfate used were increased by the moles of the increased amount of monomer a, thereby obtaining 430 g of an aqueous solution of H-type polythiophene (A2) with a concentration of 1.2 mass%.

[0128] Synthesis Example 4 In Synthesis Example 2, the amount of monomer a used was changed from 10 g to 8 g, and the amounts of anhydrous iron (III) chloride and sodium persulfate used were reduced by the moles of the reduced amount of monomer a. Except for this, the same operation as in Synthesis Example 1 was carried out to obtain 103 g of an aqueous solution of H-type polythiophene (A3) with a concentration of 5 mass%.

[0129] Synthesis Example 5. The aqueous solution of H-type polythiophene (A1) (concentration 0.74% by mass) obtained in Synthesis Example 2 was concentrated to prepare a 2.2% by mass aqueous solution of H-type polythiophene (A1). 5.8 g of a methanol solution of trioctylamine (concentration 20% by mass) was added to 300 g of the 2.2% by mass aqueous solution, and the mixture was stirred to obtain a composition containing the polythiophene (A) and trioctylamine. Thereafter, water and methanol were removed by vacuum filtration to obtain a solid, which is a composition containing the polythiophene (A) and trioctylamine. 1 g of the solid was mixed and stirred in 99 g of 1-methoxy-2-propanol (PGME) to obtain a PGME solution of amine-type polythiophene (A4) with a concentration of 1% by mass.

[0130] Synthesis Example 6. The aqueous solution of H-type polythiophene (A1) (concentration 0.74% by mass) obtained in Synthesis Example 2 was concentrated to prepare a 2.2% by mass aqueous solution of H-type polythiophene (A1). 5.8 g of a methanol solution of dioctylamine (concentration 20% by mass) was added to 300 g of the 2.2% by mass aqueous solution, and the mixture was stirred to obtain a composition containing the polythiophene (A) and dioctylamine. Thereafter, water and methanol were removed by vacuum filtration to obtain a solid, which is a composition containing the polythiophene (A) and dioctylamine. 1 g of the solid was mixed and stirred in 99 g of 1-methoxy-2-propanol (PGME) to obtain a PGME solution of amine-type polythiophene (A5) with a concentration of 1% by mass.

[0131] Synthesis Example 7. The aqueous solution of H-type polythiophene (A1) (concentration 0.74% by mass) obtained in Synthesis Example 2 was concentrated to prepare a 2.2% by mass aqueous solution of H-type polythiophene (A1). 5.8 g of a methanol solution of dioctylamine (concentration 20% by mass) was added to 300 g of the 2.2% by mass aqueous solution, and the mixture was stirred to obtain a composition containing the polythiophene (A) and dioctylamine. Thereafter, water and methanol were removed by vacuum filtration to obtain a solid, which is a composition containing the polythiophene (A) and dioctylamine. 1 g of the solid was mixed and stirred in 99 g of N-methyl-2-pyrrolidone (NMP) to obtain an NMP solution of amine-type polythiophene (A5) with a concentration of 1% by mass.

[0132] Example 1. The aqueous solution of H-type polythiophene (A1) with a concentration of 0.74% by mass obtained in Synthesis Example 2 was concentrated to prepare an aqueous solution of 2% by mass of H-type polythiophene (A1). 0.02 g of dry powdered single-walled carbon nanotubes (carbon≧80%, diameter 1.2-2.0 nm) manufactured by Sigma Aldrich as carbon nanotubes (B) and 5 g of water were added to 5 g of the above 2% by mass aqueous solution, and ultrasonic irradiation was performed for 30 minutes using an ultrasonic homogenizer (manufactured by Nippon Seiki Seisakusho Co., Ltd., US300-E) under ice cooling to obtain an electrically conductive polymer composition corresponding to the electrically conductive polymer composition according to one embodiment of the present invention. Using this electrically conductive polymer composition, an electrically conductive polymer film was produced by the method described in the above [Measurement of electrical conductivity of self-doped conductive polymer], and the electrical conductivity was measured. The results are shown in Table 1.

[0133] Example 2. 0.02 g of dry powdered single-walled carbon nanotubes (carbon≧80%, diameter 1.2-2.0 nm) manufactured by Sigma Aldrich as carbon nanotubes (B) and 1.7 g of water were added to 8.3 g of the H-type polythiophene (A2) aqueous solution having a concentration of 1.2 mass% obtained in Synthesis Example 3, and ultrasonic irradiation was performed for 30 minutes using an ultrasonic homogenizer (manufactured by Nippon Seiki Seisakusho Co., Ltd., US300-E) under ice cooling to obtain a composition corresponding to the conductive polymer composition according to one embodiment of the present invention. Using this conductive polymer composition, a conductive polymer film was produced by the method described in the above [Conductivity measurement of self-doped conductive polymer], and the conductivity was measured. The results are shown in Table 1.

[0134] Example 3. 0.02g of dry powdered single-walled carbon nanotubes (carbon≧80%, diameter 1.2-2.0nm) manufactured by Sigma Aldrich as carbon nanotubes (B) and 8g of water were added to 2g of the H-type polythiophene (A3) aqueous solution having a concentration of 5% by mass obtained in Synthesis Example 4, and ultrasonic irradiation was performed for 30 minutes using an ultrasonic homogenizer (manufactured by Nippon Seiki Seisakusho Co., Ltd., US300-E) under ice cooling to obtain a composition corresponding to the conductive polymer composition according to one embodiment of the present invention. Using this conductive polymer composition, a conductive polymer film was produced by the method described in the above [Conductivity measurement of self-doped conductive polymer], and the conductivity was measured. The results are shown in Table 1.

[0135] Example 4. 0.02 g of dry powdered single-walled carbon nanotubes (carbon≧80%, diameter 1.2-2.0 nm) manufactured by SigmaAldrich was added as carbon nanotubes (B) to 10 g of PGME solution of amine-type polythiophene (A4) with a concentration of 1% by mass obtained in Synthesis Example 5, and ultrasonic irradiation was performed for 30 minutes using an ultrasonic homogenizer (manufactured by Nippon Seiki Seisakusho, US300-E) under ice cooling to obtain a composition corresponding to the conductive polymer composition according to one embodiment of the present invention. Using this conductive polymer composition, a conductive polymer film was produced by the method described in the above [Conductivity measurement of self-doped conductive polymer], and the conductivity was measured. The results are shown in Table 1.

[0136] Example 5. 0.02 g of dry powdered single-walled carbon nanotubes (carbon≧80%, diameter 1.2-2.0 nm) manufactured by Sigma Aldrich was added as carbon nanotubes (B) to 10 g of PGME solution of amine-type polythiophene (A5) with a concentration of 1% by mass obtained in Synthesis Example 6, and ultrasonic irradiation was performed for 30 minutes using an ultrasonic homogenizer (manufactured by Nippon Seiki Seisakusho, US300-E) under ice cooling to obtain a composition corresponding to the conductive polymer composition according to one embodiment of the present invention. Using this conductive polymer composition, a conductive polymer film was produced by the method described in the above [Conductivity measurement of self-doped conductive polymer], and the conductivity was measured. The results are shown in Table 1.

[0137] Example 6. 0.02 g of dry powdered single-walled carbon nanotubes (carbon≧80%, diameter 1.2-2.0 nm) manufactured by Sigma Aldrich was added as carbon nanotubes (B) to 10 g of NMP solution of amine-type polythiophene (A5) with a concentration of 1% by mass obtained in Synthesis Example 7, and ultrasonic irradiation was performed for 30 minutes using an ultrasonic homogenizer (manufactured by Nippon Seiki Seisakusho Co., Ltd., US300-E) under ice cooling to obtain a composition corresponding to the conductive polymer composition according to one embodiment of the present invention. Using this conductive polymer composition, a conductive polymer film was produced by the method described in the above [Conductivity measurement of self-doped conductive polymer], and the conductivity was measured. The results are shown in Table 1.

[0138] Example 7. A conductive polymer composition and a conductive polymer film were obtained and evaluated in the same manner as in Example 1, except that the amount of the 2% by mass aqueous solution of H-type polythiophene (A1) was changed from 5 g to 0.5 g and the amount of water was changed from 5 g to 9.5 g in Example 1. The results are shown in Table 1.

[0139] Example 8. A conductive polymer composition and a conductive polymer film were obtained and evaluated in the same manner as in Example 1, except that the amount of the 2% by mass aqueous solution of H-type polythiophene (A1) was changed from 5 g to 2.5 g and the amount of water was changed from 5 g to 7.5 g in Example 1. The results are shown in Table 1.

[0140] Example 9. A conductive polymer composition and a conductive polymer film were obtained and evaluated in the same manner as in Example 1, except that the amount of the 2 mass% aqueous solution of H-type polythiophene (A1) was changed from 5 g to 10 g and the amount of water was changed from 5 g to 0 g in Example 1. The results are shown in Table 1.

[0141] Comparative Example 1 5.00g of water was added to 5.00g of the H-type polythiophene (A1) aqueous solution with a concentration of 2% by mass obtained by adjusting the concentration, and ultrasonic irradiation was performed for 30 minutes using an ultrasonic homogenizer (manufactured by Nippon Seiki Seisakusho, US300-E) under ice cooling to obtain a composition that does not correspond to the conductive polymer composition of the present invention. Using this composition, a conductive polymer film was produced by the method described in the above [Conductivity measurement of self-doped conductive polymer], and the conductivity was measured. The results are shown in Table 2.

[0142] Comparative Example 2 1.7 g of water was added to 8.3 g of the H-type polythiophene (A2) aqueous solution having a concentration of 1.2 mass% obtained in Synthesis Example 3, and ultrasonic irradiation was performed for 30 minutes using an ultrasonic homogenizer (manufactured by Nippon Seiki Seisakusho, US300-E) under ice cooling to obtain a composition that does not correspond to the conductive polymer composition of the present invention. Using this composition, a conductive polymer film was produced by the method described in the above [Conductivity measurement of self-doped conductive polymer], and the conductivity was measured. The results are shown in Table 2.

[0143] Comparative Example 3. 8 g of water was added to 2 g of the H-type polythiophene (A3) aqueous solution having a concentration of 5% by mass obtained in Synthesis Example 4, and ultrasonic irradiation was performed for 30 minutes using an ultrasonic homogenizer (manufactured by Nippon Seiki Seisakusho, US300-E) under ice cooling to obtain a composition that does not correspond to the conductive polymer composition of the present invention. Using this composition, a conductive polymer film was produced by the method described in the above [Conductivity measurement of self-doped conductive polymer], and the conductivity was measured. The results are shown in Table 2.

[0144] Comparative Example 4. 10 g of the PGME solution of amine-type polythiophene (A4) with a concentration of 1% by mass obtained in Synthesis Example 5 was subjected to ultrasonic irradiation for 30 minutes under ice cooling using an ultrasonic homogenizer (manufactured by Nippon Seiki Seisakusho, US300-E) to obtain a composition that does not correspond to the conductive polymer composition of the present invention. Using this composition, a conductive polymer film was produced by the method described above in [Conductivity measurement of self-doped conductive polymer], and the conductivity was measured. The results are shown in Table 2.

[0145] Comparative Example 5. 10 g of the PGME solution of amine-type polythiophene (A5) with a concentration of 1% by mass obtained in Synthesis Example 6 was subjected to ultrasonic irradiation for 30 minutes under ice cooling using an ultrasonic homogenizer (manufactured by Nippon Seiki Seisakusho, US300-E) to obtain a composition that does not correspond to the conductive polymer composition of the present invention. Using this composition, a conductive polymer film was produced by the method described above in [Measurement of the conductivity of a self-doped conductive polymer], and the conductivity was measured. The results are shown in Table 2.

[0146] Comparative Example 6. 10 g of the NMP solution of amine-type polythiophene (A5) with a concentration of 1% by mass obtained in Synthesis Example 7 was subjected to ultrasonic irradiation for 30 minutes under ice cooling using an ultrasonic homogenizer (manufactured by Nippon Seiki Seisakusho, US300-E) to obtain a composition that does not correspond to the conductive polymer composition of the present invention. Using this composition, a conductive polymer film was produced by the method described above in [Conductivity measurement of self-doped conductive polymer], and the conductivity was measured. The results are shown in Table 2.

[0147] Comparative Example 7. 0.02 g of dry powdered single-walled carbon nanotubes (carbon≧80%, diameter 1.2-2.0 nm) manufactured by Sigma Aldrich as carbon nanotubes (B) was added to 9.98 g of water, and ultrasonic irradiation was performed for 30 minutes under ice cooling using an ultrasonic homogenizer (manufactured by Nippon Seiki Seisakusho, US300-E) to obtain a composition that does not correspond to the conductive polymer composition of the present invention. Using this composition, a conductive film was produced by the method described in the above [Conductivity measurement of self-doped conductive polymer], and the conductivity was measured. The results are shown in Table 2.

[0148] Comparative Example 8. 9.98g of PGME was added to 0.02g of dry powdered single-walled carbon nanotubes (carbon≧80%, diameter 1.2-2.0nm) manufactured by Sigma Aldrich as carbon nanotubes (B), and ultrasonic irradiation was performed for 30 minutes under ice cooling using an ultrasonic homogenizer (manufactured by Nippon Seiki Seisakusho, US300-E) to obtain a composition that does not correspond to the conductive polymer composition of the present invention. Using this composition, a conductive film was produced by the method described in the above [Conductivity measurement of self-doped conductive polymer], and the conductivity was measured. The results are shown in Table 2.

[0149] Comparative Example 9. 0.02 g of dry powdered single-walled carbon nanotubes (carbon≧80%, diameter 1.2-2.0 nm) manufactured by Sigma Aldrich as carbon nanotubes (B) was added with 9.98 g of NMP, and ultrasonic irradiation was performed for 30 minutes under ice cooling using an ultrasonic homogenizer (manufactured by Nippon Seiki Seisakusho, US300-E) to obtain a composition that does not correspond to the conductive polymer composition of the present invention. Using this composition, a conductive film was produced by the method described in the above [Conductivity measurement of self-doped conductive polymer], and the conductivity was measured. The results are shown in Table 2.

[0150] Comparative Example 10. 0.02 g of dry powdered single-walled carbon nanotubes (carbon≧80%, diameter 1.2-2.0 nm) manufactured by Sigma Aldrich was added as carbon nanotubes (B) to 10 g of PEDOT / PSS aqueous solution (aqueous dispersion with a solid content concentration of 1% by mass), and ultrasonic irradiation was performed for 30 minutes using an ultrasonic homogenizer (manufactured by Nippon Seiki Seisakusho Co., Ltd., US300-E) under ice cooling to obtain a composition that does not correspond to the conductive polymer composition of the present invention. Using this composition, a conductive film was prepared by the method described in [Conductivity measurement of self-doped conductive polymer] above, and the conductivity was measured. The results are shown in Table 2.

[0151] Comparative Example 11. A 1% by mass aqueous solution of poly(4-styrenesulfonic acid) (PSS) solution (weight average molecular weight 75,000, aqueous dispersion with a solid content of 18% by mass) manufactured by Sigma Aldrich was concentrated to prepare a 1% by mass aqueous solution of PSS. 0.02 g of dry powdered single-walled carbon nanotubes (carbon ≧80%, diameter 1.2-2.0 nm) manufactured by Sigma Aldrich was added as carbon nanotubes (B) to 10 g of the above aqueous solution of PSS, and ultrasonic irradiation was performed for 30 minutes using an ultrasonic homogenizer (manufactured by Nippon Seiki Seisakusho Co., Ltd., US300-E) under ice cooling to obtain a composition that does not correspond to the conductive polymer composition of the present invention. Using this composition, a conductive film was prepared by the method described in the above [Conductivity measurement of self-doped conductive polymer], and the conductivity was measured. The results are shown in Table 2.

[0152] Comparative Example 12. 9.9 g of water was added to 0.1 g of polyacrylic acid (weight average molecular weight 5,000) manufactured by Fujifilm Wako Pure Chemical Industries, to prepare a polyacrylic acid aqueous solution having a solid content concentration of 1% by mass. 0.02 g of dry powdered single-walled carbon nanotubes (carbon≧80%, diameter 1.2-2.0 nm) manufactured by Sigma Aldrich was added as carbon nanotubes (B) to 10 g of the above polyacrylic acid aqueous solution, and ultrasonic irradiation was performed for 30 minutes using an ultrasonic homogenizer (manufactured by Nippon Seiki Seisakusho, US300-E) under ice cooling to obtain a composition that does not correspond to the conductive polymer composition of the present invention. Using this composition, a conductive film was prepared by the method described in the above [Conductivity measurement of self-doped conductive polymer], and the conductivity was measured. The results are shown in Table 2.

[0153] Comparative Example 13. 10 g of PEDOT / PSS aqueous solution (aqueous dispersion with a solid content concentration of 1% by mass) was irradiated with ultrasonic waves for 30 minutes under ice cooling using an ultrasonic homogenizer (manufactured by Nippon Seiki Seisakusho, US300-E) to obtain a composition that does not correspond to the conductive polymer composition of the present invention. Using this composition, a conductive film was produced by the method described in [Conductivity measurement of self-doped conductive polymer] above, and the conductivity was measured. The results are shown in Table 2.

[0154] Comparative Example 14. A 1% by mass aqueous solution of PSS was prepared by concentrating a poly(4-styrenesulfonic acid) (PSS) solution (weight average molecular weight: 75,000, aqueous dispersion with a solid content of 18% by mass) manufactured by Sigma Aldrich. 10 g of the above aqueous PSS solution was subjected to ultrasonic irradiation for 30 minutes under ice cooling using an ultrasonic homogenizer (manufactured by Nippon Seiki Seisakusho, US300-E) to obtain a composition that does not correspond to the conductive polymer composition of the present invention. Using this composition, a conductive film was produced by the method described above in [Conductivity measurement of self-doped conductive polymer], and the conductivity was measured. The results are shown in Table 2.

[0155] Comparative Example 15. 9.9 g of water was added to 0.1 g of polyacrylic acid (weight average molecular weight 5,000) manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. to prepare an aqueous polyacrylic acid solution having a solid content concentration of 1% by mass. 10 g of the above aqueous polyacrylic acid solution was subjected to ultrasonic irradiation for 30 minutes under ice cooling using an ultrasonic homogenizer (manufactured by Nippon Seiki Seisakusho Co., Ltd., US300-E) to obtain a composition that does not correspond to the conductive polymer composition of the present invention. Using this composition, a conductive film was produced by the method described in the above [Conductivity measurement of self-doped conductive polymer], and the conductivity was measured. The results are shown in Table 2.

[0156] [Table 1]

[0157] [Table 2]

[0158] As shown in Tables 1 and 2, the carbon nanotubes (B) contained in the conductive polymer composition according to one embodiment of the present invention were in a good dispersion state. Moreover, the conductivity of the conductive polymer film produced using the conductive polymer composition according to one embodiment of the present invention was increased compared to the case where a composition not corresponding to the conductive polymer composition of the present invention was used.

[0159] Furthermore, it was found that in the conductive polymer composition according to one embodiment of the present invention, when the polythiophene (A) was 0.1 mass %, i.e., when the carbon nanotubes (B) were 2 mass parts per mass part of the polythiophene (A), the electrical conductivity was extremely high, on the order of four orders of magnitude.

[0160] As shown in Table 3, the carbon nanotubes (B) aggregated in the composition containing PEDOT / PSS, a conventional conductive polymer. The carbon nanotubes (B) in the composition containing PSS had good dispersibility but low conductivity. The composition containing polyacrylic acid showed the same results as in the case of PSS.

[0161] The remarkable improvement in electrical conductivity described above is based on the action specific to the conductive polymer composition according to one embodiment of the present invention, and shows a unique effect not seen in the past. [Industrial Applicability]

[0162] The conductive polymer composition according to one embodiment of the present invention can provide a conductive polymer film containing carbon nanotubes that has significantly superior electrical conductivity compared to conventionally known carbon nanotube dispersions that require an insulating dispersant.

[0163] Therefore, the conductive polymer composition and conductive polymer film according to one embodiment of the present invention can be used as an antistatic agent, a solid electrolyte for an aluminum capacitor or a tantalum capacitor, an antistatic film, or a separator for a wound-type aluminum electrolytic capacitor. In addition, the conductive polymer composition and conductive polymer film can be expected to be applied to electrochromic elements, transparent electrodes, transparent conductive films, thermoelectric conversion materials, photoelectric conversion elements, chemical sensors, actuators, electromagnetic wave shielding materials, microwave heat-generating paints, or positive or negative electrode materials for secondary battery materials, etc.

Claims

1. A conductive polymer composition comprising 0.01 to 5 mass % of polythiophene (A) containing at least two or more structural units selected from the group consisting of a structural unit represented by the following general formula (1) and a structural unit represented by the following general formula (2), and comprising 0.016 to 0.5 mass % of carbon nanotubes (B): 【Chemistry 1】 [In the above general formulas (1) and (2), R 2 represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom, m represents an integer of 1 to 10, and n represents 0 or 1.

2. 2. The conductive polymer composition according to claim 1, wherein the carbon nanotubes (B) are at least one selected from the group consisting of single-walled carbon nanotubes, double-walled carbon nanotubes, and multi-walled carbon nanotubes.

3. The conductive polymer composition according to claim 1 , wherein the carbon nanotubes (B) are single-walled carbon nanotubes.

4. 2. The conductive polymer composition according to claim 1, wherein the content of the polythiophene (A) is 0.05 to 0.8 mass %.

5. 2. The conductive polymer composition according to claim 1, wherein the content of the carbon nanotubes (B) is 0.016 to 0.21 mass %.

6. 2. The conductive polymer composition according to claim 1, wherein a composition ratio of the polythiophene (A) to the carbon nanotubes (B) is 0.5 to 3 parts by mass of the carbon nanotubes (B) per 1 part by mass of the polythiophene (A).

7. 2. The conductive polymer composition according to claim 1, wherein a composition ratio of the polythiophene (A) to the carbon nanotubes (B) is 1 to 2.5 parts by mass of the carbon nanotubes (B) per 1 part by mass of the polythiophene (A).

8. 10. A method for producing a conductive polymer film, comprising applying the conductive polymer composition according to claim 1 onto a support and then drying the applied composition.

9. A conductive polymer film comprising: a polythiophene (A) containing at least one structural unit selected from the group consisting of a structural unit represented by the following general formula (1) and a structural unit represented by the following general formula (2); and carbon nanotubes (B), wherein a compositional ratio of the polythiophene (A) to the carbon nanotubes (B) is 0.5 to 3 parts by mass of the carbon nanotubes (B) per 1 part by mass of the polythiophene (A). 【Chemistry 2】 [In the above general formulas (1) and (2), R 2 represents a hydrogen atom, a methyl group, an ethyl group, a linear or branched alkyl group having 3 to 6 carbon atoms, or a fluorine atom, m represents an integer of 1 to 10, and n represents 0 or 1.

10. The conductive polymer film according to claim 9, wherein the composition ratio of the polythiophene (A) to the carbon nanotubes (B) is 1 to 2.5 parts by mass of the carbon nanotubes (B) per 1 part by mass of the polythiophene (A).

Citation Information

Patent Citations

  • Carbon nanotube dispersion liquid comprising conductive polymer, carbon material and method for producing the dispersion liquid

    JP2016026983A